The expanded collagen VI family: new chains and new questions. (22nd August 2013) - Fitzgerald, Jamie; Holden, Paul; Hansen, Uwe
Abstract: Collagen VI is a component of the extracellular matrix of almost all connective tissues, including cartilage, bone, tendon, muscles and cornea, where it forms abundant and structurally unique microfibrils organized into different suprastructural assemblies. The precise role of collagen VI is not clearly defined although it is most abundant in the interstitial matrix of tissues and often found in close association with basement membranes. Three genetically distinct collagen VI chains, α1(VI), α2(VI) and α3(VI), encoded by the COL6A1. COL6A2 and COL6A3 genes, were first described more than 20 years ago. Their molecular assembly and role in congenital muscular dystrophy has been broadly characterized. In 2008, three additional collagen VI genes arrayed in tandem at a single gene locus on chromosome 3q in humans, and chromosome 9 in mice, were described. Following the naming scheme for collagens the new genes were designated COL6A4. COL6A5 and COL6A6 encoding the α4(VI), α5(VI) and α6(VI) chains, respectively. This review will focus on the current state of knowledge of the three new chains.